Seasonal variations of male reproductive parameters of Tomodon dorsatus from Southeastern Brazil - Abud, Luciane Lily [UNESP]; Schimming, Bruno Cesar [UNESP] (Colégio Brasileiro de Patologia Animal - CBPA, 2021)
The morphology of the male reproductive tract of Tomodon dorsatus was described in the austral seasons of the year considering macroscopic and microscopic variables. For this purpose, 56 specimens from the herpetological collection of the “Instituto Butantan” were used. Fragments of the testes, kidneys and ductus deferens were collected and submitted to histological routine. The peak of the testicular volume was observed in the summer and the epithelium of the seminiferous tubules had higher height in the summer (p=0.001). The testes were active throughout the year, however, the spermiogenesis peaked in the summer. There were spermatozoa in the lumen of the ductus deferens in all seasons of the year. Renal length was higher in autumn (p=0.027), and renal width did not show a significant increase (p=0.237). The diameter and epithelial height of the sexual segment of the kidney (SSK) showed hypertrophy in winter and spring, coinciding with the mating period. Based on findings of this study, we can suggest that, at the population level, the reproductive cycle of T. dorsatus can be considered seasonal semi-synchronous, due to the peak of spermiogenic activity in the hot season, and discontinuous at the individual level.

A morfologia do trato reprodutivo do macho de Tomodon dorsatus foi descrita nas estações climáticas do ano com base em variáveis macroscópicas e microscópicas. Para isto, foram usados 56 espécimes oriundos da coleção herpetológica do Instituto Butantan. Fragmentos dos testículos, rins e ductos deferentes foram coletados e submetidos à rotina histológica. O volume testicular foi maior no verão e o epitélio dos túbulos seminíferos mostrou uma maior altura no verão (p=0.001). Os testículos estavam ativos durante todo o ano, contudo, a espermiogênese foi maior no verão. Espermatozoides foram encontrados no lúmen do ducto deferente em todas as estações do ano. O comprimento renal foi maior no outono (p=0.027), e a largura renal não mostrou um aumento significativo (p=0.237). O diâmetro e a altura epitelial do segmento sexual do rim (SSR) mostrou hipertrofia nas estações inverno e primavera, coincidindo com o período reprodutivo. Com base nestes resultados, pode-se sugerir que, em nível populacional, o ciclo reprodutivo de T. dorsatus possa ser considerado semi-sincrônico sazonal, devido à atividade espermiogênica na estação quente, e descontínuo em nível individual.
Variações sazonais dos parâmetros reprodutivos do macho de Tomodon dorsatus do sudeste brasileiro
Keywords: Reproduction; Tomodon dorsatus; Brazil; snake; sexual segment; kidney; testis; wildlife animals; Reprodução; Tomodon dorsatus; serpentes; segmento sexual; rim; testículo; animais selvagens